1999
DOI: 10.1038/sj.bjc.6690180
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan expression in gastric cancer cells is associated with local and nodal spread and reduced survival rate

Abstract: Hyaluronan (HA), an extracellular high-molecular-mass polysaccharide, is supposed to be involved in the growth and progression of malignant tumours. We studied the cellular expression of HA in 215 operated stage I–IV gastric cancer patients using a specific biotinylated probe. Most (93%) of the tumours showed HA staining in their parenchyma, whereas the stroma inside and around the tumour was stained in every case. When HA expression was compared with the clinical and histological features of the tumours, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(73 citation statements)
references
References 29 publications
4
66
1
Order By: Relevance
“…[13][14][15][16][17][18][19] We found that the HA staining had 92.3% sensitivity and 80.6% specificity to predict biochemical recurrence within 112 months. Interestingly, the specificity of HA staining to predict biochemical recurrence increased from 61% at 72-month follow-up to 80.6% at 112-month follow-up.…”
Section: Evaluation Of the Prognostic Capability Of Pre-and Postoperamentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17][18][19] We found that the HA staining had 92.3% sensitivity and 80.6% specificity to predict biochemical recurrence within 112 months. Interestingly, the specificity of HA staining to predict biochemical recurrence increased from 61% at 72-month follow-up to 80.6% at 112-month follow-up.…”
Section: Evaluation Of the Prognostic Capability Of Pre-and Postoperamentioning
confidence: 99%
“…14 The concentration of HA is elevated in several tumor types, and in some tumors (e.g., breast, colon), high-level HA expression in tumor-associated stroma and/or tumor cells predicts poor survival. [15][16][17][18][19] Increased urinary HA levels serve as an accurate diagnostic marker for bladder cancer, regardless of tumor grade and stage. 20 However, in PCa, HA is not an independent predictor for prognosis.…”
mentioning
confidence: 99%
“…Accumulation of HA has been reported in a wide variety of human tumors, including those of the prostate, colon, breast, stomach, ovary, and pancreas (6)(7)(8)(9)(10)(11)(12). Elevated HA (stromal and/or pericellular staining) in tumor biopsies has been correlated with local invasion, the presence of distal metastasis, higher tumor grade, and poorer overall survival (13).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of hyaluronic acid are elevated in cancers of the breast, colon, prostate, bladder, etc. (8,(12)(13)(14)(15)(16)(17)(18). In tumor tissues, elevated hyaluronic acid is mostly localized to tumor stroma; however, in some tumors, including bladder cancer, it is also expressed in tumor cells (12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%